Arts and Culture for all in Public Libraries: Reflections from the front-line (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
I have worked in community library services for the past 27 years and have seen the role of libraries in promoting and supporting cultural activity change and develop significantly over the period.  All libraries are generally defined as a physical space that holds specific resources for use by its members.  A typical definition of a public library can be found at collinsdictionary.com: 'a building where things such as books, newspapers, videos and music are kept for people to read, use or borrow'.  When I began working in public libraries, much of my role supported this simple definition. The majority of my work involved the maintenance and development of library collections and the ways in which they could be more easily accessed by users.  Over the years, the priorities of front-line staff in libraries have moved away from a collection-centred approach towards an approach that is more community-centred.  There have been a number of factors that have contributed to this change in emphasis but, from my perspective, they all have their roots in libraries adjusting to community demand.